Kim on Emergence - Shoemaker, Sydney (Philosophical studies, 2002)
Emergence requires that the ultimate physical micro-entities have "micro-latent" causal powers, which manifest themselves only when the entities are combined in ways that are "emergence-engendering," in addition to the "micro-manifest" powers that account for their behavior in other circumstances. Subjects of emergent properties will have emergent micro-structural properties, specified partly in terms of these micro-latent powers, each of which will be determined by a micro-structural property specified only in terms of the micro-manifest powers of the constituents and the way they are related. If the determiner and the determined properties are distinct, this determination is the basis of the supervenience of emergent properties on non-emergent physical properties. If not, emergence does not involve such supervenience. Either way, there is no problem with diachronic downward causation.